150k views
4 votes
Can anyone answer this questionin 4 Step I'll mark that person has branily​ please

Can anyone answer this questionin 4 Step I'll mark that person has branily​ please-example-1

1 Answer

3 votes

Answer:


- (11)/(28)

Explanation:


(2)/(5) \bigg( - (3)/(7) \bigg) - (1)/(6) * (3)/(2) + (1)/(14) * (2)/(5) \\ \\ </p><p></p><p></p><p>= - (6)/(35) - (3)/(12) + (1)/(35) \\ \\ </p><p></p><p></p><p>= (1 - 6)/(35) - (1)/(4) \\ \\ </p><p></p><p>= ( - 5)/(35) - (1)/(4) \\ \\ </p><p></p><p>= ( - 1)/(7) - (1)/(4) \\ \\ </p><p></p><p>= ( - 1* 4-1* 7)/(7* 4) \\\\</p><p>= ( - 4- 7)/(28) \\\\</p><p>= -( 11)/(28) \\\\</p><p>

User Fabian Barney
by
5.0k points